A Social Sketch of Radical Islamism in Solo - wildan, muhammad (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2013)
This article examines phenomena of Islamic radicalism in Solo based on the social facts in the city. The assessment is important in tracing the origins of Islamic radicalism in Solo recently. By bibliographical study of Islamic movement and field study in the region, this study describes and analyzes the formats of Islamic radicalism in Solo and its impacts in political situation in Indonesia. This comprehension on the emergence of this radicalism, according to the writer, could bring to the solving of the problems and the prevention of surfacing Islamic radicalism in the future.